A digital and nurse-led support intervention, first year after prostate cancer treatment: a single-arm feasibility study in a Swedish primary care setting - Nazmije Kelmendi; Ann Langius-Eklöf; Marina Taloyan; Kay Sundberg; Åsa Craftman; Marie Nilsson (BMC Primary Care)
Abstract Background The prevalence of patients with prostate cancer is increasing, and the first year after treatment is a vulnerable period for patients as they experience symptoms and unmet needs. Although electronic patient-reported outcomes that focus on patient self-management have demonstrated benefits, evidence is sparse regarding patients with prostate cancer in primary care settings and the role of nurses as a supportive resource. The significant role of primary care in future cancer care is on the agenda. This study aims to test the feasibility of a complex intervention that includes electronic patient-reported outcomes and self-management advice in an app, combined with nurse-led support, in primary care settings during the first year after curative intended prostate cancer treatment. Methods The intervention lasted four weeks and was a single-arm study. Feasibility was assessed by examining the recruitment process, retention rate, adherence to the reporting of symptoms in the app, and acceptability of the intervention. Data was collected through (1) logged data from the app that included patient-reported outcomes and self-management advice, (2) field notes by the nurse, and (3) semi-structured interviews with patients. Descriptive statistics were applied to logged data. The interviews and the field notes were analysed using qualitative content analysis. Results The recruitment rate was 55%, yielding 11 patients with high retention as all completed the intervention. Adherence to reporting was 100%, and all functions in the app were used. Individual variation in how patients used the app was found, which was attributed to patients’ current needs. In total, 36 health dialogues with the nurse (virtual, face-to-face, telephone) were performed; all first dialogues lasted longer, while follow-ups were shorter. Patients described that the health dialogues covered relevant subjects and that the combination of using the app and health dialogues was tailored and provided supplementary support. No adverse events occurred; however, a few technical difficulties interfered with the intervention, and the patients gave valuable suggestions for improvement. Furthermore, patients suggested that the intervention should start immediately after treatment. Conclusion As the patients adhered to and accepted the intervention, it was considered feasible. Findings suggest intervention should start directly after treatment ends.